Terms of trade : glossary of international economics - Deardorff, Alan V. (World Scientific, 2014)
Have you ever wondered what a term in international economics means? This useful reference book offers a glossary of terms in both international trade and international finance, with emphasis on economic issues. It is intended for students getting their first exposure to international economics, although advanced students will also find it useful for some of the more obscure terms that they have forgotten or never encountered. Besides an extensive glossary of terms that has been expanded about 50% from the first edition, there is a picture gallery of diagrams used to explain key concepts such as the Edgeworth Production Box and the Offer Curve Diagram in international economics. This section is followed by over 30 lists of terms that occur a lot in international economics, grouped by subject to help users find terms that they cannot recall. Prior to an enlarged bibliography is an expanded section on the origins of terms in international economics, which records what the author has been able to learn about the origins of some of the terms used in international economics. This is a must-have portable glossary in international trade and international economics!